THE PRINCIPAL’S EFFORTS TO INCREASE THE MOTIVATION AND PERFORMANCE OF TEACHERS AT SDN 005 SEI BERAS-BERAS - Umi Khaeriyah (JURNAL PAJAR (Pendidikan dan Pengajaran), 2020)
This study aims to improve teacher motivation and performance. This research is a qualitative descriptive study that describes the conditions of motivation and performance of the teachers of SDN 005 Sei Beras, totaling 12 people. The research was carried out from October to November 2019. The instruments used in this study were observation and interviews. The results showed that the teacher's motivation in the first cycle had an average of 75.83 which was classified as high category, in the second cycle it reached an average of 84.58 which was included in the very high category. It can be concluded that the teacher's efforts can increase teacher motivation and performance. The efforts made by the principal to increase teacher motivation and performance are through creating a conducive work atmosphere, rewarding teachers who have achievements and innovations in improving school quality, and striving for the provision of facilities and infrastructure that can support learning activities in schools.